Genome‐wide screening for DNA variants associated with reading and language traits. (29th August 2014) - Gialluisi, A.; Newbury, D. F.; Wilcutt, E. G.; Olson, R. K.; DeFries, J. C.; Brandler, W. M.; Pennington, B. F.; Smith, S. D.; Scerri, T. S.; Simpson, N. H.; ,; Luciano, M.; et al.
Abstract : Reading and language abilities are heritable traits that are likely to share some genetic influences with each other. To identify pleiotropic genetic variants affecting these traits, we first performed a genome‐wide association scan (GWAS) meta‐analysis using three richly characterized datasets comprising individuals with histories of reading or language problems, and their siblings. GWAS was performed in a total of 1862 participants using the first principal component computed from several quantitative measures of reading‐ and language‐related abilities, both before and after adjustment for performance IQ. We identified novel suggestive associations at the SNPs rs59197085 and rs5995177 (uncorrected P ≈ 10 –7 for each SNP), located respectively at the CCDC136 / FLNC and RBFOX2 genes. Each of these SNPs then showed evidence for effects across multiple reading and language traits in univariate association testing against the individual traits. FLNC encodes a structural protein involved in cytoskeleton remodelling, while RBFOX2 is an important regulator of alternative splicing in neurons. The CCDC136/FLNC locus showed association with a comparable reading/language measure in an independent sample of 6434 participants from the general population, although involving distinct alleles of the associated SNP. Our datasets will form an important part of on‐going international efforts to identify genes contributing to reading and language skills. Abstract : Genome‐wide association scan meta‐analysis for reading and language ability.